THE USE OF DIGITAL TECHNOLOGIES IN THE ORGANIZATION OF MODERN EDUCATION - Usmanov Murod Sadikovich (Web of Journals Publishing, 2024)
In today's world, one of the main challenges is to provide modern education to young people and thus ensure the sustainable development of the country. It is a fact that in today's fast-paced world, learning how to access and use information has become a major goal for young people.
Keywords: digital technology, modernity, educational technologies, modern education, educational institutions.